Accumulation and toxicity of monoaromatic petroleum hydrocarbons in early life stages of cod and haddock. (August 2019) - Sørensen, Lisbet; Hansen, Bjørn Henrik; Farkas, Julia; Donald, Carey E.; Robson, William J.; Tonkin, Andrew; Meier, Sonnich; Rowland, Steven J.
Abstract: A multitude of recent studies have documented the detrimental effects of crude oil exposure on early life stages of fish, including larvae and embryos. While polycyclic aromatic hydrocarbons (PAHs), particularly alkyl PAHs, are often considered the main cause of observed toxic effects, other crude oil derived organic compounds are usually overlooked. In the current study, comprehensive two-dimensional gas chromatography coupled to mass spectrometry was applied to investigate the body burden of a wide range of petrogenic compounds in Atlantic haddock ( Melanogrammus aeglefinus ) and cod ( Gadus morhua ) embryos that had been exposed to sublethal doses of dispersed crude oil. Several groups of alkylated monoaromatic compounds (e.g. alkyl tetralins, indanes and alkyl benzenes), as well as highly alkylated PAHs, were found to accumulate in the fish embryos upon crude oil exposure. To investigate the toxicity of the monoaromatic compounds, two models (1-isopropyl-4-methyltetralin and 1-isopropyl-4-methylindane) were synthesized and shown to bioaccumulate and cause delayed hatching in developing embryos. Minor developmental effects, including craniofacial and jaw deformations and pericardial edemas, were also observed at the highest studied concentrations of the alkylindane. Graphical abstract: Image 1 Highlights: Monoaromatic compounds were found to accumulate in crude oil exposed haddock and cod embryos. Two model compounds were synthesized and bioconcentration and toxicity tested using passive dosing. Monoaromatic compounds displayed sublethal toxicity towards haddock embryos. Abstract : Crude oil derived monoaromatic hydrocarbons accumulate in fish early life stages and may contribute to overall toxicity.